Development of Output Feedback Sliding Mode Control for Nonlinear System With Disturbance - Md Nawawi, Mohamad Riduwan; Chong, Shin Horng; Hashim, Mohd. Ruzaini; Hanafi, Ainain Nur (2011)
This paper discusses about the development of output feedback Sliding Mode Control (SMC) and demonstrate that this controller is able to reject disturbance in a nonlinear system. The designed SMC controller works well to ensure system stability and eliminates disturbance in linear and nonlinear dynamics systems. The approach to develop output feedback controller is by implementing High Gain Observer and the output performance from this controller is compared with the output response from the state feedback SMC. Both designed controllers are constructed in simulation by using MATLAB SIMULINK tool. The required gains involve in the designed control laws are tuned heuristically by trial and error approach. The state response results obtained from the simulations are analyzed. Based on the observation and analysis to the results it shows that the output feedback SMC illustrate s smooth state response and reduces the effect of disturbance as provided by the state feedback (SMC) without disturbance.